2010
DOI: 10.1111/j.1365-2966.2010.16698.x
|View full text |Cite
|
Sign up to set email alerts
|

Parsec-scale SiO emission in an infrared dark cloud

Abstract: We present high‐sensitivity 2 × 4 arcmin2 maps of the J= 2→1 rotational lines of SiO, CO, 13CO and C18O, observed towards the filamentary infrared dark cloud (IRDC) G035.39−00.33. Single‐pointing spectra of the SiO J= 2→1 and J= 3→2 lines towards several regions in the filament are also reported. The SiO images reveal that SiO is widespread along the IRDC (size ≥2 pc), showing two different components: one bright and compact arising from three condensations (N, E and S) and the other weak and extended along th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 50 publications
8
135
1
Order By: Relevance
“…As supported by the observed line wings, SiO emission is probably caused by outflow activity which generates shocks releasing SiO into the gas phase. However, some of the widespread SiO emission could result from shocks associated with cloud formation as suggested in the IRDC G035.39-00.33 (Jiménez-Serra et al 2010). The SiO abundances derived for our clumps are mostly comparable to those seen in other IRDCs (Vasyunina et al 2011;Sanhueza et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As supported by the observed line wings, SiO emission is probably caused by outflow activity which generates shocks releasing SiO into the gas phase. However, some of the widespread SiO emission could result from shocks associated with cloud formation as suggested in the IRDC G035.39-00.33 (Jiménez-Serra et al 2010). The SiO abundances derived for our clumps are mostly comparable to those seen in other IRDCs (Vasyunina et al 2011;Sanhueza et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that the submm peaks G1.87−SMM 28, 30, and 38 are coincident with the local SiO peak positions. Jiménez-Serra et al (2010) proposed that the extended SiO emission they observed along the filamentary IRDC G035.39-00.33 is the result of a low-velocity shock produced by colliding flows (see also Henshaw et al 2013). The widespread SiO emission could therefore originate in the cloud formation process instead of during star formation.…”
Section: Sio (Silicon Monoxide)mentioning
confidence: 99%
“…Theories involving production of dense gas in shocks have been supported by detection of large-scale SiO emission along IRDCs (Jiménez-Serra et al 2010;Nguyen-Lu'o'ng et al 2013). However, these studies focus only on a few individual clouds and are still confined to few-parsec scales in and around the filamentary molecular clouds.…”
Section: Introductionmentioning
confidence: 93%
“…Motte et al 2007;Sakai et al 2010). However, an interesting recent study by Jiménez-Serra et al (2010) shows that the SiO emission towards the IR-dark cloud G35.39-0.33 is extended on parsec scale, suggesting widespread low-mass star formation. A&A 526, L2 (2011) Observations towards low-mass protostars so far point to an evolutionary picture in which jets are always associated with Class 0 objects (e.g.…”
Section: Introductionmentioning
confidence: 99%